Acclimatization of a newly isolated bacteria in monomer tere-phthalic acid (TPA) may enable it to attack the polymer poly-ethylene tere-phthalate(PET). Issue 4 (August 2020) - Kumar, Vinay; Maitra, S.S.; Singh, Rekha; Burnwal, Dilip Kumar
Graphical abstract: Abstract: Environmental persistence of polyethylene terephthalate(PET) has become a vexing problem. PET is a very popular polymer for many desirable properties, especially as a food grade polymer. It is being produced in large quantities and the entire production is not recycled. A large quantity of PET is finding its way to the Municipal Solid Waste (MSW) dumps and even to rivers as microplastics. There are various methods for PET degradation, among which bio-degradation is most environmentally friendly and technologically suitable. Some metagenomic studies have been conducted for isolation of PET degrading bacteria/enzymes. However, all previous studies deal with bacteria directly isolated from contaminated sites. We have isolated one such bacteria Rhococcus sp. SSM1 from a PET rich MSW dump of New Delhi. However, we did not use the bacteria directly for PET degradation. We forced the bacteria to grow on the monomer terephpthalic acid(TPA), the monomer, as the only carbon source for generations. Surprisingly, the Rhococcus sp. SSM1 acclimatized to grow on TPA, was able to attack PET flims, the polymer, resulting in some degradation of the material. This was evidenced by presence of more TPA concentration than supplied at certain time of fermentation and many heavy molecules (heavier than TPA) in the fermentation media which can only come only by degradation of PET. This is a new paradigm in biodegradation research, where acclimatization in the monomer enables a bacteria to attack the polymer. However, we are not claiming that the bacteria can biodegrade bulk PET. It is perhaps surviving on TPA and attacking the surface of the polymer, which is microscopically rough. Bacteria may be recognizing some protruding fingers di, tri or n-mers of TPA from polymer surface and attacking them.